The Effect of Box Explosion Media on Student Learning Interest in Islamic Education Learning in Medan City - Lubis, Chairunnisa; Sapri, Sapri (Universitas Muhammadiyah Ponorogo, 2024)
Education shapes good people, yet low interest and student involvement are issues. This may be caused by lack of preparation, laziness, indifference in learning, and poor learning goal awareness. Box Explosion media is used in Islamic Religious Education (PAI) Class VIII SMP Muhammadiyah 48 Medan to engage pupils. Based on this context, this research investigates if Box Explosion media affects students' interest in Islamic Religious Education (PAI) Class VIII SMP Muhammadiyah 48 Medan. This research investigated if Box Explosion Media affects students' learning interest in Islamic Religious Education (PAI) Class VIII SMP Muhammadiyah 48 Medan School Year 2023/2024. This study is quantitative and experimental. Nonequivalent Group Posttest Only Design is used for Quasi Experimental Design. Study participants were Class VIII SMP Muhammadiyah 48 Medan. Purposive sampling was used to choose 60 pupils from class VIII-Hisyam and VIII-Ibrahim. Based on data analysis using the Hypothesis test (t) with the help of IBM SPSS Statistic 25, it can be seen that the significance value is 0.000<0.005 which means that the independent variable has a significant effect on the dependent variable with the average interest in the control class is 50.33 while the average in the experimental class is 58.47, meaning that there is an increase in interest in learning in students when the use of Box Explosion learning media is carried out. So it can be concluded that there is an effect of using Box Explosion media on students' interest in learning in the subject of Islamic Religious Education (PAI) Class VIII SMP Muhammadiyah 48 Medan School Year 2023/2024.